Graduated colour tape measure: Development and demonstration of this tool in a case series of neonatal skin injuries. Issue 3 (August 2019) - August, Deanne; Hitchcock, Ian; Tangney, Janelle; Ray, Robin A.; Kandasamy, Yoga; New, Karen
Abstract: Aim: This study proposed to (1) develop a metric graduated colour tool and (2) demonstrate the effectiveness of the tool for use in the assessment of neonatal skin injuries. Materials/methods: Findings from wound literature informed the metric graduated colour tool's development. Tool development included consideration of colours, size (comparative to neonatal skin injuries), cost, materials, feasibility and suitability for the neonatal clinical setting. Assessment of the tool's applicability with clinical images was then tested using digital cameras with specific evaluation of image sharpness and colour. Further evaluation was conducted within a case series of neonatal skin injuries. Results: The metric graduated colour tool comprised of 15 colours, measures 60 mm, displays metric dimensions, and offers a discernible reference for clinical images and injury/wound bed comparison. Images collected appeared enhanced with clear wound edges compared to previous methods. Four neonates who acquired skin injuries were included in the case series for which the tool provided reliable metric and colour comparison of epidermal stripping, extravasation, birth injury, and pressure injury. When used to compare injury assessments for series subjects measurements of both increased and decreased severity were obtained. Conclusion: A metric and colour tool can be used in conjunction with digital photographs to enhance objective assessment of neonatal skin injuries/wounds. The metric and colour tool provides the foundation for vital skin injury assessment and documentation essentials including injury bed colour, size and consideration of depth of damage. Highlights: Neonatal skin injury assessment of size and severity is challenging due to gaps in assessment standardization. MGC Tool design considered colour, size, cost, material, feasibility and suitability for the neonatal clinical setting. MGC tool: measures 60 mm, displays 15 colours, metric dimensions, and offers reference for injury assessment and images.